Exploring the Nature of Humanity and Its Relationship with Education in Shaping the Character and Civilization - Hendrizal, Hendrizal; An Shoriah, Kamilah; Lovita, Nuria; Putri, Rini Irmata; Asmelawati, Asmelawati; Sasmiyarti, Sasmiyarti; Wati, Juliarika (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This study aims to explore the essence of humanity and its connection to education in shaping character and civilization. The focus of the research is to understand how education can develop cognitive, emotional, social, and moral dimensions that contribute to building strong character and advancing civilization. The methodology used is a qualitative descriptive approach with a literature review, analyzing educational theories and literature from various experts, such as Hattie (2022), Dweck (2022), and Freire (2020). The findings indicate that holistic education, which encompasses both cognitive and moral aspects, is crucial in shaping individuals who are not only intelligent but also responsible and ethical. The concepts of growth mindset, character education, as well as social awareness and inclusivity play key roles in forming individuals who are ready to face the challenges of the era. Integrative education, which includes digital literacy and respect for diversity, has also proven to prepare individuals to contribute to social improvement and the development of civilization. This study concludes that education that emphasizes the development of character and moral values will shape individuals who are more adaptable and capable of building a better society.